Re-imagining Africa: revisiting Rider Haggard’s legacy in modern times with particular reference to South Africa - Lindy STIEBEL (E-REA)
Haggard’s significance as a barometer of his age as a popular writer and as a writer of interest for the modern age still holds true. This article revisits some of the themes of that statement and assesses Haggard’s ongoing legacy in the modern era. It will draw on my books Imagining Africa: landscape in H. Rider Haggard’s African romances (2001) and also on the Introduction to Lives of Victorian Literary Figures: H. Rider Haggard (2009), a commissioned volume, which also evaluated Haggard’s legacy both in terms of academic interest and popular culture in the later twentieth century. My interest in writing this current piece is to look again at Haggard a decade on and update my earlier findings with contemporary references to Haggard, in terms of his literary, popular culture and academic legacies.